Inventory of lianas and their phorophytes in Desa Serdang village forest, Barusjahe, Karo, North Sumatra - Rizanti Aulan Wazuhratun Lubis; Wina Dyah Puspita Sari; Yusran Efendi Ritonga (LPPM Universitas Negeri Jakarta, 2024)
As Indonesia is known as a megabiodiversity country, and Sumatra is its second largest island, it is important to understand its ever-threatened plant biodiversity, including those managed locally as village forests. In Serdang Village Forest, Barusjahe, Karo, North Sumatra, we tried to list all the liana species and their phorophytes. We conducted a qualitative descriptive analysis of the lianas and their phorophytes in the study area and found There are 25 species of lianas from 14 families Mostly are leaners, followed by tendril climbers, root climbers, hook climbers, thorn climbers and twiners. They climbed on 8 species of phorophyte from 8 families, most commonly tall forest trees. This study enhances our understanding of the lianas and their phorophytes in the Serdang Village Forest, which can aid conservation efforts to preserve biodiversity.